#TITLE_ALTERNATIVE# - TIFFANO ; Pembimbing Utama : Prof. Dr. Ir. Komang Bagiasna, YEADY
In industrial world today, one of the most recognized technique used for maintenance of rotating equipment is predictive maintenance based on vibration signal. This kind of predictive maintenance is able to identify type of failure that occurred in a rotating equipment. The type of failure can be identified through its vibration signal, because every failure has their own unique characteristics. One of the most common problem encountered in rotating equipment was misalignment between two shaft that connected by a coupling. In practice, the vibration signal characteristics used to identify misalignment problem was based only on statistics data of the equipment failure record. Vibration signal generation in misalignment case is a complex mechanism and involving various parameter. The most significant parameter is the type of coupling being used. Different type of coupling will generate different vibration signal characteristics. Theoretical explanation about the mechanism of vibration signal generation due to misalignment was still less in number. The scope of study in this thesis will be limited only in a case of parallel misalignment on a shaft system connected with rigid mechanical coupling. Experimental evaluation was done on a setup that was made by Manurung [5]. Experimental evaluation was done in several offset value which are 0 mm, 0.1 mm, 0.2 mm and 0.3 mm. Offset was given in horizontal and vertical direction. During experiment, the rotating frequency was varied. The variation were 10 Hz, 15 Hz, 20 Hz, 25 Hz and 30 Hz. The number of bolt used to connect the rigid coupling was also being varied. The coupling was connected using two and four bolt. Measurement of vibration response was done on the bearing using accelerometer and on the coupling using LASER Doppler Vibrometer. Theoretical analysis was done by recalculating the model that was developed by A. W. Lees. The increase pattern of vibration magnitude due to parallel misalignment seen most clearly on the frequency of 1xRPM. It was found both on theoretical analysis and experimental result. The presence of parallel misalignment in horizontal direction will affect vibration response in the vertical direction, and on the contrary, the presence of parallel misalignment in vertical direction will affect vibration response in the horizontal direction.